2014
DOI: 10.1371/journal.pone.0090168
|View full text |Cite
|
Sign up to set email alerts
|

Road Salts as Environmental Constraints in Urban Pond Food Webs

Abstract: Freshwater salinization is an emerging environmental filter in urban aquatic ecosystems that receive chloride road salt runoff from vast expanses of impervious surface cover. Our study was designed to evaluate the effects of chloride contamination on urban stormwater pond food webs through changes in zooplankton community composition as well as density and biomass of primary producers and consumers. From May – July 2009, we employed a 2×2×2 full-factorial design to manipulate chloride concentration (low = 177 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 48 publications
7
44
1
Order By: Relevance
“…Elevated chloride concentrations in lakes can alter the composition and function of phytoplankton, zooplankton, macroinvertebrate, and fish communities (10)(11)(12)35). As a consequence of salinization, aquatic species richness and abundance may decline, which could result in trophic cascades and altered water quality and ecosystem structure and function (36).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated chloride concentrations in lakes can alter the composition and function of phytoplankton, zooplankton, macroinvertebrate, and fish communities (10)(11)(12)35). As a consequence of salinization, aquatic species richness and abundance may decline, which could result in trophic cascades and altered water quality and ecosystem structure and function (36).…”
Section: Significancementioning
confidence: 99%
“…Although chloride concentrations in freshwaters can vary cyclically due to climatic processes, such as extended periods of drought (6), elevated chloride concentrations in lakes often result from agricultural, industrial, and transportation practices (7). Elevated chloride concentrations can have adverse effects on water quality and aquatic ecosystems (8)(9)(10)(11), including both immediate and long-term alterations to community structure, diversity, and productivity (12)(13)(14).…”
mentioning
confidence: 99%
“…Salinity is known as a driving force governing the composition of aquatic ecological communities (Gunter 1956), and recent work has suggested that salinity can affect the interactions of amphibians with other community members (e.g., food-web dynamics) both directly and indirectly (Petranka and Doyle 2010;Chambers 2011;Van Meter et al 2011;Petranka and Francis 2013;Moreira et al 2015;Van Meter and Swan 2014). Adaptation to salinity could certainly lead to novel predation opportunities for amphibians in these environments, as has been shown in some South American anurans eating marine invertebrates, for example (Sazima 1971;Brasileiro et al 2010;Ferreira and Tonini 2010).…”
Section: Origins Of Salt Tolerancementioning
confidence: 99%
“…In addition to lethal effects, exposure of freshwater animals to elevated chloride concentrations in the 100s or 1,000s of mg/L can induce of a suite of sublethal effects. These effects include osmoregulatory disruption (Karraker & Gibbs, 2011a), diminished growth and development (Johnson et al., 2015), increased malformations and disease susceptibility (Brady, 2013; Hopkins, French, & Brodie, 2013; Karraker & Ruthig, 2009), and behavioral changes (Hall et al., 2017), all of which can influence fitness, community dynamics, and ecosystem function (Schuler et al., 2017; Van Meter & Swan, 2014). …”
Section: Introductionmentioning
confidence: 99%